2023
DOI: 10.1161/circinterventions.123.013083
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Transcatheter Aortic Valve Replacement for Aortic Stenosis in Patients With Type 0 Bicuspid, Type 1 Bicuspid, and Tricuspid Aortic Valves

Jingjing He,
Tian-Yuan Xiong,
Yi-Jun Yao
et al.

Abstract: BACKGROUND: Data concerning the outcomes of transcatheter aortic valve replacement in type 0 bicuspid aortic stenosis (AS) are scarce. The study aims to compare the outcomes of transcatheter aortic valve replacement for AS in patients with type 0 bicuspid, type 1 bicuspid, and tricuspid aortic valve anatomy. METHODS: We enrolled consecutive patients undergoing transcatheter aortic valve replacement for severe AS between 2012 and 2022 in this single-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In our retrospective analysis we reported good procedural and short‐term clinical outcomes, without significant differences in terms of periprocedural complications, 30‐days and 1‐year clinical outcomes between the two groups, confirming the previous results of the BEAT Registry 19 . He et al recently reported favorable short‐term clinical outcomes after TAVI, mainly using SEV (91.4%), in patients with BAV type 0 (25.8%) and type 1 (23.7%), without significant difference in terms of mortality and major complications as compared to matched TAV patients (50.5%) 22 . In our population the percentage of BAV type 0 was very low, so we cannot offer statement regarding this specific subgroup.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our retrospective analysis we reported good procedural and short‐term clinical outcomes, without significant differences in terms of periprocedural complications, 30‐days and 1‐year clinical outcomes between the two groups, confirming the previous results of the BEAT Registry 19 . He et al recently reported favorable short‐term clinical outcomes after TAVI, mainly using SEV (91.4%), in patients with BAV type 0 (25.8%) and type 1 (23.7%), without significant difference in terms of mortality and major complications as compared to matched TAV patients (50.5%) 22 . In our population the percentage of BAV type 0 was very low, so we cannot offer statement regarding this specific subgroup.…”
Section: Discussionsupporting
confidence: 82%
“…and type 1 (23.7%), without significant difference in terms of mortality and major complications as compared to matched TAV patients (50.5%). 22 In our population the percentage of BAV type 0 was very low, so we cannot offer statement regarding this specific subgroup. Overall, we observed similar rate of all-cause mortality (3.4% vs. 1.7%) and stroke (2% vs. 0.9%) at 30 days.…”
Section: Discussionmentioning
confidence: 69%
“…Several propensity-matched studies, which diminish intrinsic baseline differences, have demonstrated equivalent 1-year mortality and incidence of moderate or severe PVL between bicuspid and tricuspid aortic valves using second-generation devices, as well as in low surgical risk patients. [ 12 ] However, current results are mainly derived from Sievers’ Type 1 bicuspid morphology, whereas the underpresented Type 0 subtype has recently been associated with a higher probability of elevated residual transvalvular gradients but a lower incidence of pacemaker implantation and PVL, [ 13 ] suggesting different behaviors among bicuspid subtypes.…”
mentioning
confidence: 99%